Features of determining clinical signs in the process of differential diagnosis in patients with suspected temporomandibular disorder - Makeyev Валентин Федорович; Telishevska Оксана Дмитрівна; Mykhailevych Марта Юріївна (Actual Dentistry, 2020)
Summary. Despite a large number of studies on the diagnosis and treatment of these disorders, a unified strategy among researchers has not yet been determined. It is difficult for practitioners to determine the etiology and pathogenesis of heart failure and the fact that information on the development factors of these diseases is contradictory, there is no general opinion on the results of studying this problem, and the data presented in various publications are usually ambiguous and even contradictory. The etiology and pathogenesis of heart failure remains not fully understood, therefore, finding ways to treat this pathology is often difficult, because understanding the etiology of temporomandibular disorders is extremely important in recognizing and eliminating potential pathological factors. The goal of the study was to determine the clinical diagnostic criteria and their significance in the differential diagnosis of temporomandibular disorders and diseases, which can imitate or may indicate the possibility of rejection of the diagnosis of heart failure. Results. It was revealed that for the proportion of people with limited opening of the mouth (less than 4 cm), the most characteristic symptom was in the subgroup with arthrogenic (35.1 % of arthrogenic contrary contrary 7.1 % in the comparison group, p < 0.01) and myogenic (18.8 % of myogenic contrary 7.1 % in the comparison group, p < 0.05) disorders. For combined disorders, this indicator was statistically unreliable (p > 0.05). An increase (more than 5 cm) in mouth opening by comparing the persons of the main group and the persons of the comparison group was not statistically likely (20.0 % contrary 25.0 %, p > 0.05). It was determined that such a symptom as deviation (left and right) for the subgroup «arthrogenic disorders» was 40.7 % contrary 17.9 % in the comparison group (p < 0.05), for the subgroup «myogenic disorders» 25.0 % contrary 17.9 % in the comparison group (p > 0.05), for the group of «combined disorders» 42.3 % contrary 17.9 % (p < 0.05). In terms of deflection (left and right), the proportion of people with arthrogenic disorders with this symptom was 74.3 % contrary 7.1 % in the comparison group (p < 0.01). For myogenic disorders, this indicator was not reliable (6.25 % contrary 7.1 %; p < 0.05), and for combined disorders it was 15.4 % contrary 7.1 % in the comparison group (p < 0.05). So, the studies have identified and confirmed the importance of a thorough clinical examination of patients with suspected temporomandibular disorder, which allows at this stage to carry out preliminary differential diagnosis between truly heart failure and patients who imitate or question the presence of temporomandibular disorder. Conclusions. Among patients with confirmed temporomandibular disorders, a number of clinical symptoms were identified that are statistically confirmed compared with persons in whom diseases mimicking TMD were identified or this diagnosis was rejected.